Poética da profanação: um estudo de A obscena senhora D, de Hilda Hilst - Mattos, Suzana Freire de (2021)
This dissertation proposes to wander through the writing of A obscena senhora D, by Hilda Hilst, in regard to the profanation of the literary text in the transubstantiation of the symbols into poetic incarnated word. In order to contextualize the corpus, we bring the concept of a poetics of postmodernism in the sense of a paradox. In the paradox that resides between the axis of tradition and rupture, the corpus extends itself as a literary project inserted in the world of the existence, in the breach between the real and the fictional, generating dissonant movements which intensity breaks with the dualistic values of the society. The multiple connections based around the same symbols manifest themselves simultaneously through the sacred and the profane of the words around the existence, bringing the poles into tension through the poetic language, architecting different entries to the text, possible beyond the interpretative reading. In its literary function, the novel transgresses the syntax of the phrase, in an incessant rhythm, is iconoclast by nature, undoing the crystallization and promoting an infinite unveiling of the self as an another. The poetic work is engaged in the juxtaposition of symbols that move in the interval of the language. Based upon the overlap of imagens in process of shattering, the movement itself is a desire for the continuity of life through the poetic word, and lays bare the rhizomatic aspect of the language able to move from the sacred to the profane, opening itself up to poetic nature of all words. In the poetics of profanity, the pleasure of the language is reconnected to the sacred, in which aspect the incarnated word becomes a sacramental word